(untitled) (Acta Scientiarum. Technology, 2012)
The large volume of sugar cane vinasse generated by alcohol distillation motivated current treatment to reduce vinasse volume by a concentration process and to eliminate pollutants in the wastewater. The vinasse concentration by the coagulation/flocculation process favored the use of the thickened sludge either for fertilizing purposes or for biogas production. The photocatalysis treatment of the clarified vinasse mineralized pollutants and reduced toxicity, with subsequent water reuse. The first series of coagulation/flocculation experiments were carried out in a jar-test apparatus at room temperature with samples of 200 mL and several coagulant concentrations. In the second series of experiments, photocatalysis tests were performed on the clarified vinasse obtained by coagulation/flocculation under conditions optimized in the first series of experiments. The photocatalysis tests were performed for five consecutive days with UV irradiation, using TiO2-P25 as photocatalyst. Significant reduction of toxicity, consistent with the reduction in chemical oxygen demand (COD), was found when the photocatalysis treatment subsequent to coagulation/flocculation process was employed. Further, 98% reduction of turbidity and 87% reduction of color were obtained by the coagulation/flocculation process. Coupled to the photocatalysis process, significant reductions in absorbance, toxicity and COD (80%) were also achieved. Â